Halogen activation in the plume of Masaya volcano: field observations and box model investigations - Rüdiger, Julian; Gutmann, Alexandra; Bobrowski, Nicole; Liotta, Marcello; de Moor, J. Maarten; Sander, Rolf; Dinger, Florian; Tirpitz, Jan-Lukas; Ibarra, Martha; Saballos, Armando; Martínez, María; Mendoza, Elvis; et al. (Atmospheric chemistry and physics, 2021)
Volcanic emissions are a source of halogens in the atmosphere. Rapid reactions convert the initially emitted hydrogen halides (HCl, HBr, and HI) into reactive species such as BrO, Br, BrCl, ClO, OClO, and IO. The activation reaction mechanisms in the plume consume ozone which is entrained by ambient air that is mixed into the plume. In this study, we present observations of the oxidation of bromine, chlorine, and iodine during the first 11 min following emission, examining the plume from Santiago crater of the Masaya volcano in Nicaragua. Two field campaigns were conducted: one in July 2016 and one in September 2016. The sum of the reactive species of each halogen was determined by gas diffusion denuder sampling followed by gas chromatography-mass spectrometry (GC-MS) analysis, whereas the total halogens and sulfur concentrations were obtained by alkaline trap sampling with subsequent ion chromatography (IC) and inductively coupled plasma mass spectrometry (ICP-MS) measurements. Both ground and airborne sampling with an unoccupied aerial vehicle (carrying a denuder sampler in combination with an electrochemical SO2 sensor) were conducted at varying distances from the crater rim. The in situ measurements were accompanied by remote sensing observations (differential optical absorption spectroscopy; DOAS). The reactive fraction of bromine increased from 0.20 ± 0.13 at the crater rim to 0.76 ± 0.26 at 2.8 km downwind, whereas chlorine showed an increase in the reactive fraction from (2.7 ± 0.7) × 10−4 to (11 ± 3) × 10−4 in the first 750 m. Additionally, a reactive iodine fraction of 0.3 at the crater rim and 0.9 at 2.8 km downwind was measured. No significant change in BrO /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="6bfc4ae3491d603d986b6e1d0e6866cf"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-3371-2021-ie00001.svg" width="8pt" height="14pt" src="acp-21-3371-2021-ie00001.png"/></svg:svg> SO2 molar ratios was observed with the estimated age of the observed plume ranging from 1.4 to 11.1 min. This study presents a large complementary data set of different halogen compounds at Masaya volcano that allowed for the quantification of reactive bromine in the plume of Masaya volcano at different plume ages. With the observed field data, a chemistry box model (Chemistry As A Boxmodel Application Module Efficiently Calculating the Chemistry of the Atmosphere; CAABA/MECCA) allowed us to reproduce the observed trend in the ratio of the reactive bromine to total bromine ratio. An observed contribution of BrO to the reactive bromine fraction of about 10 % was reproduced in the first few minutes of the model run.
Gesehen am 27.08.2021